(untitled) (Eurasian Research Bulletin, 2022)
The current study included diagnosing microcystins their concentrations in the waters of the Shatt al-Arab River, as well as in the algal biomass of three sites along the stream of the river, namely Al-Siba, Al-Ashar and Al-Haritha. Water samples were collected monthly for each site for a full year, starting in October 2020 until September 2021. The current study included measuring some physical and chemical environmental factors on a monthly basis in the three study sites, The average air temperature ranged from 31.5 °C in the Al-Ashar site to 28 °C in the Siba site, As for the water temperature, there were no significant differences between the study sites, the pH values tended to be neutral between the sites, as the pH rates ranged from 7.1 in the Al-Siba site during the month of June to 8.7 in the Al-Haritha site during the month of September, The average salinity concentrations ranged from 0.53 g/L at Al-Haritha site during the month of September to 22.06 g/L at Al-Siba site during the month of July. During this study, the concentrations of some important nutrients such as active nitrate and active phosphate were measured. The nitrate levels ranged from 14.1 μg/L in Siba site during the month of October to 0.01 μg/L in the same site, while for the effective phosphate values it ranged between 2.24 μg/L at Al-Haritha site during the month of September to 0.01 µg/liter in Siba site during the months of October. The results of the study showed that the highest concentration of hepatotoxins in the biomass of phytoplankton throughout the study period was in Al-Haritha site during the month of June, reaching 5.5 µg/L, while the lowest concentration of these toxins was in Al-Ashar site, reaching 0.1 µg/L during the month of March, in When the highest concentration of hepatotoxins in the Shatt al-Arab waters was 4.8 µg/Lin AL-Siba site during the month of February, and the lowest concentration was in the months of March, September and June in AL-Siba, Al-Ashar and Al-Haritha, respectively, as it amounted to less than 0.15 µg/L. In this study, it was found that some of those environmental factors measured during the study period had an effect on the concentrations of hepatotoxins (MCs) in the phytoplankton biomass in the Shatt Al-Arab River through a significant positive correlation with salinity concentrations at Al-Haritha site, and a significant negative correlation with the air and water temperature in the AL-Siba site also at the probability level P≤0.01, while the concentrations of those toxins at the level of significance P≤0.05 in the Shatt Al-Arab water were not related to any of those factors. This study also showed that the concentrations of nutrients of nitrates and phosphates did not have a clear effect on the concentrations of hepatotoxic MCs in the phytoplankton biomass and water in the Shatt Al-Arab River